RANCANG BANGUN ALAT PENGERING KERUPUK UBI UNGU UNTUK MENINGKATKAN KAPASITAS PRODUKSI - Whydiantoro; Engkos Koswara; Budiman; Asep Rachmat (Jurnal Ilmiah Teknologi Infomasi Terapan, 2025)
The raw cracker dryer is designed against several problem identifications found in the surrounding environment so that it can be utilised and used as effectively and efficiently as possible, the tool made takes less than 50 minutes as a whole in the roasting room to reach a temperature of more than 43°C streamline the time and place of heating crackers. In this research, it will be studied how to design a purple sweet potato cracker dryer that suits the needs of the community, which does not require excessive electrical energy. Because the capacity of electrical energy owned by umkm is very limited at a maximum of 900 VA. The heating device is designed with the main frame using Stinles Steel 400 can also be called hollow iron connected with a welding process with a size of 1200 mm long, 700 mm wide, 900 mm high and the distance between the pans is 300 mm. The test results show that the heating device takes less than 60 minutes as a whole in the heating chamber to reach a temperature of more than 43°C.